2022
DOI: 10.1002/ange.202201882
|View full text |Cite
|
Sign up to set email alerts
|

Active Mechanical Threading by a Molecular Motor**

Abstract: Molecular motors transform external energy input into directional motions and offer exquisite precision for nano-scale manipulations. To make full use of molecular motor capacities, their directional motions need to be transmitted and used for powering downstream molecular events. Here we present a macrocyclic molecular motor structure able to perform repetitive molecular threading of a flexible tetraethylene glycol chain through the macrocycle. This mechanical threading event is actively powered by the motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…19 Lightdriven mechanical threading of a flexible tetraethylene glycol chain through a macrocycle was realized in a hemithioindigobased molecular motor. 20 Similarly, coupling between rotary and reciprocating motion on the nanoscale was demonstrated using a [1]rotaxane whose two components (macrocycle and shaft) were connected to the two halves of a molecular motor (Figure 1D), 21 mimicking a reverse reciprocating engine, powered not by the reciprocating but by the rotary motion. An earlier example used a stiff-stilbene 22 co-workers by demonstrating active and unidirectional acceleration of biaryl rotation using a molecular motor (Figure 1E).…”
Section: ■ Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…19 Lightdriven mechanical threading of a flexible tetraethylene glycol chain through a macrocycle was realized in a hemithioindigobased molecular motor. 20 Similarly, coupling between rotary and reciprocating motion on the nanoscale was demonstrated using a [1]rotaxane whose two components (macrocycle and shaft) were connected to the two halves of a molecular motor (Figure 1D), 21 mimicking a reverse reciprocating engine, powered not by the reciprocating but by the rotary motion. An earlier example used a stiff-stilbene 22 co-workers by demonstrating active and unidirectional acceleration of biaryl rotation using a molecular motor (Figure 1E).…”
Section: ■ Introductionmentioning
confidence: 92%
“…A study on a different second-generation motor featuring an extended aromatic core revealed a helix inversion coupled to its rotation as a byproduct of the steric clash in the newly introduced extended lower half (Figure C) . Light-driven mechanical threading of a flexible tetraethylene glycol chain through a macrocycle was realized in a hemithioindigo-based molecular motor . Similarly, coupling between rotary and reciprocating motion on the nanoscale was demonstrated using a [1]­rotaxane whose two components (macrocycle and shaft) were connected to the two halves of a molecular motor (Figure D), mimicking a reverse reciprocating engine, powered not by the reciprocating but by the rotary motion.…”
Section: Introductionmentioning
confidence: 98%